HUBUNGAN UKURAN LINGKAR LENGAN ATAS DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI PUSKESMAS LUBUK BUAYA PADANG - Wildayani, Desi; Sujendri, Sintia (Jurnal Ilmiah Kesehatan Ibu dan Anak, 2022)
The Padang City Health Office in 2019 found 1968 cases or around 10.6% of pregnant women with anemia. Of the 22 health centers in Padang City, the Lubuk Buaya Health Center is the second highest for pregnant women with anemia, namely 379 cases or around 17.6%. One of the causes of anemia was lack of nutrients in the food consumed. Upper Arm Circumference is an option to determine nutritional status because it is easy and fast. Upper Arm Circumference (UAC) reflects energy reserves, hence it reflects energy and calorie deficiencies (ECD) in women of childbearing age and pregnant women. This type of analytical research used a cross-sectional design, carried out on 7-10 August 2021. The total sample is 35 pregnant women. The sampling method used accidental sampling technique. Data processing were carried out by editing, coding, entry, tabling and cleaning. Then, analyzed by univariate and bivariate analysis. The results of the study were 35 out of 7 respondents with UAC <23.5 cm (ECD), there were 5 (71.4%) respondents who had anemia. Of the 28 respondents with UAC 23.5 cm (non-ECD), there were 4 (14.2%) respondents who had anemia. After statistical tests were carried out with the chi square formula, the value of p = 0.006 (p <0.05) was obtained. So, it was concluded that there was a relationship between nutritional status and the incidence of anemia in pregnant women at the Lubuk Buaya Padang Health Center in 2021. Suggestions for health workers, especially midwives and regional supervisors, to provide information directly through counseling about anemia in pregnancy, nutritional status of pregnant women and complications what will happen to the mother and fetus, such as bleeding during labor and delivery of low birth weight babies.